2021
DOI: 10.1016/j.ssmph.2021.100902
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 vaccine preference: A survey study in Japan

Abstract: Objective Vaccination is a critical measure for containing the COVID-19 pandemic. We survey the determinants that affect the preference for COVID-19 vaccines in Japan, a vaccine hesitant nation. Setting and design : We conducted a randomized conjoint analysis survey of the preference for vaccines on the Internet by recruiting a nonprobability sample of 15,000 Japanese adults. The survey assigned 5 choice tasks to the respondents. In each task, the respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…Our results showed that negative sentiment predominates positive sentiment in most time in Japan, when most previous studies of other countries exhibited more positive sentiment on social media [23,24,26]. The negative sentiment exhibited by our results consistent with the findings of some previous studies using surveys in Japan [40][41][42][43][44][45], and we provided fine-grained and more practical evidence. We observed a decrease in the correlation of negative sentiment with infection cases and death cases in Table 2, for which the direct reason is the decrease of infection and death cases and the abnormal increase of negative sentiment.…”
Section: Principal Findingssupporting
confidence: 89%
“…Our results showed that negative sentiment predominates positive sentiment in most time in Japan, when most previous studies of other countries exhibited more positive sentiment on social media [23,24,26]. The negative sentiment exhibited by our results consistent with the findings of some previous studies using surveys in Japan [40][41][42][43][44][45], and we provided fine-grained and more practical evidence. We observed a decrease in the correlation of negative sentiment with infection cases and death cases in Table 2, for which the direct reason is the decrease of infection and death cases and the abnormal increase of negative sentiment.…”
Section: Principal Findingssupporting
confidence: 89%
“…Lastly, freedom to choose which vaccine to receive, and its association with hesitancy, has been hypothesized by a few authors [47], but the issue is still under-investigated. In our study, the main drivers of choice were comparable to those found among Japanese people in February 2021 [48], except for the country of vaccine production, which we found replaced by vaccine type. This difference may relate to when the various surveys were conducted; unlike the Japanese respondents, our students were exposed to media reports in March and April 2021, alleging a worse performance for Vaxzevira (AstraZeneca AB, SödertĂ€lje, Sweden) [29], the most well-known viral-vector vaccine.…”
Section: Discussionsupporting
confidence: 77%
“…What is worst, enormous inequalities emerged in vaccine rollout, often mirroring limited access to vaccines due to financial constraints (e.g., in many countries in Africa 4 ), excessive caution in granting approval of foreign-produced drugs (e.g., in Japan 5 ), or supply problems (e.g., in Australia 4 ).…”
Section: Introductionmentioning
confidence: 99%